Deep vein thrombosis secondary to abdominal aortic aneurysm: A case report. Issue 31 (August 2019) - Goh, Zhong Ning Leonard; Seak, Joanna Chen-Yeen; Seak, Chen-Ken; Wu, Chen-Te; Seak, Chen-June
Abstract: Rationale: Abdominal aortic aneurysm is an extremely rare cause of deep vein thrombosis. Here we report an elderly gentleman who presented with deep vein thrombosis and was found to have concomitant abdominal aortic aneurysm upon ultrasonographic screening. It illustrates the possibility of such an aetiology, and the importance of screening for such aneurysms in a select patient population before heparinization. Patient concerns: A 73-year-old Asian gentleman with underlying hypertension, hyperlipidaemia, chronic renal failure, and history of chronic smoking presented to the emergency department with acute left lower limb swelling of 1 day. On examination, the patient was tachycardic (110 beats/minute) and hypertensive (168/84 millimeters mercury (mmHg)). The entire left lower limb was swollen with notable pitting oedema, tenderness, and warmth; left calf swelling was measured to be 4 centimeters (cm). Diagnoses: The patient's Wells score of 4 placed him in the high-risk group for deep vein thrombosis. Serum D-dimer was subsequently found to be elevated at 926 nanograms/milliliter (ng/ml). Compression ultrasonography revealed a thrombus in the left deep femoral vein, confirming the diagnosis of deep vein thrombosis. The ultrasonographic evaluation was extended to the abdominal aorta due to the patient's high risk of abdominal aortic aneurysm, and a 7-cm aneurysm was indeed found. Further computed tomography and magnetic resonance imaging localized it to the infrarenal region, with left common iliac vein compression resulting in stagnant venous return. Interventions: Emergency endovascular repair was performed with insertion of an inferior vena cava filter. Outcomes: The patient was subsequently monitored in the intensive care unit and uneventfully discharged after 2 weeks. Lessons: Such clinical presentations of deep vein thrombosis are rare, but physicians are reminded to consider screening for abdominal aneurysms and other anatomical causes before heparinization in patients who seemingly do not have thromboembolic risk factors. This is especially so for the high risk group of male deep vein thrombosis patients aged 65–75 years with a history of smoking who have yet to be screened for abdominal aortic aneurysms, in line with United States Preventive Services Task Force recommendations.